Aspectos de gênero e vulnerabilidade ao HIV/AIDS entre usuários de dois dos serviços de atendimento especializado em DST/AIDS de São Luís, Maranhão - MAFRA, Rogério Luís Pereira (Universidade Federal do Pará, 2018)
We examine factors that contribute to the vulnerability of men and women living with HIV/AIDS, users of the Serviço de Atendimento Especializado em DST/AIDS (SAE), examining demographic and epidemiological differences as well as their reception and access to diagnosis and treatment. We conducted an observational, descriptive and cross-sectional study, in which 248 individuals were interviewed between October and December of 2007. We applied the chi-square test and multivariate analysis by CHAID technique (significance level of 5%). We established a classification by sex. We felt that some elements of an individual, programmatic and social level, including gender, contributed significantly to the vulnerability of the respondents. We observed substantial differences between men and women, considering: employment and income, total partners and condom use. The manner of shelter and access to diagnosis and treatment in the SAE is presented as an element of increased vulnerability, for not promoting a comprehensive service to the users. We identified aspects of differential vulnerability of women in the group over the "condom use after diagnosis", associated with the type of partnership (steady or not) and "understanding of what it is been saidduring the consultations", which was directly related to service time at SAE. In this sense, a way to reduce vulnerability pervades the pursuit of gender equity, ethnicity, to improve the quality of life.